Magnus the Lawmender's Laws of the Land - Katrín Friðriksdóttir, Jóhanna (Routledge Medieval Translations, 2024)
The first English translation of Magnus the Lawmender's law code, this book allows students and scholars to interpret, compare and add their perspectives to this crucial source to European legal history. The Laws of the Land are one of the very few law books issued in the Middle Ages which regulated a whole kingdom. It stayed in force until the late 17th century, shaping society, politics and law in Norway and its surrounding regions for over 400 years. This book is separated into three parts. The first is an introduction to the laws written by the translator, Jóhanna Katrín Friðriksdóttir. The second and longest section of the book is a complete English translation of the Laws of the Land. The final part is a glossary, which lays out the most important Old Norse legal terms with English translations. The glossary also contains explanations and conversions of religious feast days which are relevant in the law. Providing familiarity with the Laws of the Land, this book is crucial to students and scholars of Medieval history alike to understanding the social, legal, political, and intellectual developments of the Nordic High Middle Ages.